Treatment of symptomatic carotid stenosis associated with asymptomatic intracranial aneurysm: Presentation of a case - López, Daniel; Valverdu, Martín; Carminatt, Susana; Gómez Fossati, Carlos (Cirugía del Uruguay, 1993)
The arteriographic finding of an asy mptomatic intracranea/ aneurysm in a palien/ who suffered from symptomatic carotid atenosis, represents a case in which carotid revascu/arization cou/d theoretically provoke aneurysm rupture.